Leadership and High Performance in Direct Sales: A Critical Appraisal of Leadership Approaches and their Connection to Sales Performance in the Arena of Direct Sales. - Teasdale, David (2011)
Direct Sales (DS) is used as a means to sell products directly to consumers in a number of billion £ Industries. It differs from other direct-‐to-‐consumer selling such as Retail and web based selling, and business-‐to-‐business selling in a variety of different ways. The main differences that characterise the DS environment are 1) The teams of salespeople tend to be very large 2) the salespeople are predominantly self-‐employed 3) DS environments are peculiarly fast-‐paced, immediate and demanding. In addition to this, the industries that employ this sales method are subject to increased market complexity, competitiveness, economic uncertainty and consumers who are becoming more demanding and savvy. It is against this backdrop that leaders in DS are continually striving to achieve high performance.